Analisis Kinerja Protokol Routing Destination Sequence Distance Vector (DSDV) dan Optimized Link State Routing (OLSR) Berdasarkan Mobilitas Gauss-Markov Pada Mobile Ad-hoc Network (MANET) - Aditya Prayudhi; Rakhmadhany Primananda; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wi-fi technology is very dependent on the infrastructures, therefore Mobile Ad-Hoc Network (MANET) arises as a solution to this problem. MANET is a network technology that can run without a centralized infrastructure. MANET also needs a protocol so that every devices can communicate with each other. DSDV and OLSR are the protocols commonly used in MANET. Simulation is needed to determine which protocol is better in a certain network condition. Researchers mainly used software simulator to help them simulate MANET because real life simulation costs too high. Mobility model is needed so that nodes in simulation can represent mobile devices properly. The example of a mobility model is gauss-markov. In this mobility model, initially the node will run with a certain speed and direction, then after some time interval the calculation of destination and speed will be carried out based on the destination and speed of the node at that time. This research examined the performance of DSDV and OLSR using the gauss-markov mobility model. The results of the tests conducted, the OLSR protocol generally has better performance. But the advantages of the DSDV protocol are lower end-to-end delay values when testing with fewer nodes and lower node speeds.